Validation of a Standardised Duplex Ultrasound Classification System for the Reporting and Grading of Peripheral Arterial Disease. (August 2022) - Huthart, Samuel; Oates, Crispian; Allen, John; Fiaschi, Kathia; Sims, Andrew J.; Stansby, Gerard
Abstract : Objective: Duplex ultrasound (DUS), a non-invasive means of arterial mapping, allows for the reliable diagnosis of peripheral arterial disease (PAD). One of the authors (C.P.O.), developed a standardised DUS based scoring system, devised for rapid detection and reporting of PAD. The purpose of this study was to validate this system, and to determine the diagnostic performance both overall and per disease severity. Methods: In total, 250 participants were recruited, based on diagnosis of ( n = 125) or absence of PAD ( n = 125) from general practice registers. Right and left legs per subject were handled as independent readings, determining actual PAD status via ankle brachial pressure index (ABPI) < 0.9, and then further grading disease severity using suggested ABPI ranges. Data were excluded if no corresponding ABPI value was obtained per DUS determination or if the ABPI reading was > 1.4, owing to the risk of false negatives due to incompressible vessels. Diagnostic sensitivity and specificity were obtained overall, and per severity classification. Furthermore, inter-rater agreement between ABPI and DUS determined PAD severity was determined by linear weighted Cohen's kappa. Results: The sensitivity and specificity in the detection of disease overall was 81.0% (95% confidence interval [CI] 73.4 – 87.2) and 86.3% (95% CI 82.3 – 89.8), respectively. From mild to severe PAD, sensitivity increased from 71.1% (95% CI 55.7 – 83.6) to 89.3% (95% CI 71.8 – 97.7). Furthermore, a Cohen's kappa value of 0.63 (95% CI 0.57 – 0.69) was obtained, indicating moderate agreement between the two diagnostic methods. Conclusion: The findings of this study validate the diagnostic performance of the standardised DUS scoring system, as well as its capacity to grade severity of disease, offering a potential tool for the identification of PAD in community/research settings following initial screening methods. Confirmatory work could include a comparison of DUS determined disease with gold standard methods of non-invasive angiography, and novel tools such as toe flex near infrared spectroscopy and multisite photoplethysmography.